Failure of sucrose replacement with the non-nutritive sweetener erythritol to alter GLP-1 or PYY release or test meal size in lean or obese people. (1st December 2016) - Overduin, Joost; Collet, Tinh-Hai; Medic, Nenad; Henning, Elana; Keogh, Julia M.; Forsyth, Faye; Stephenson, Cheryl; Kanning, Marja W.; Ruijschop, Rianne M.A.J.; Farooqi, I. Sadaf; van der Klaauw, Agatha A.
Abstract: There is considerable interest in the effect of foods containing high intensity sweeteners on satiation. However, less is known about low-calorie bulk sweeteners such as erythritol. In this randomized three-way crossover study, we studied 10 lean and 10 obese volunteers who consumed three test meals on separate occasions: (a) control sucrose meal; (b) isovolumic meal with partial replacement of sucrose by erythritol; (c) isocaloric meal which contained more erythritol but equivalent calories to the control meal. We measured gut hormone levels, hunger and satiety scores, ad libitum food intake, sucrose preference and intake after the manipulations. There was a greater post-prandial excursion in glucose and insulin levels after sucrose than after the erythritol meals. There was no difference in GLP-1/PYY levels or subsequent energy intake and sucrose preference between sucrose control and isovolumic erythritol meals. In lean (but not obese) participants, hunger decreased to a greater extent after the isocaloric erythritol meal compared to the control meal (p = 0.003) reflecting the larger volume of this meal. Replacing sucrose with erythritol leads to comparable hunger and satiety scores, GLP-1 and PYY levels, and subsequent sucrose preference and intake.